2014
DOI: 10.1177/0021998314557533
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fibre misalignment and voids on composite laminate strength

Abstract: This article studies the effects of manufacturing defects of laminate composite materials on the first ply failure load and ultimate strength of the laminate, which are calculated using finite element modelling with Zinoviev’s damage model. The following types of defects are considered for cross-ply and quasi-isotropic layups: in-plane misalignement and out-of-plane waviness of fibres, misorientation of the layers and void content. The list of laminates studied in this article includes cross-ply and quasi-isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…Misalignment angles ranging from 1 to 68 were observed to lead to a reduction in compressive strength from 1.9 to 1.5 GPa. Similarly, Fedulov et al (2015) reported a 16 % reduction in ultimate compression load for a fiber misalignment of 58 in carbon/epoxy composites, along with a linear reduction in failure initiation load due to misalignment. Furthermore, Vallons et al (2011) reported tensile property reductions for a biaxial non-crimp fabric composite at small off-axis angles.…”
Section: Adverse Effects Of Fiber Misalignment On Mechanical Propertiesmentioning
confidence: 85%
See 4 more Smart Citations
“…Misalignment angles ranging from 1 to 68 were observed to lead to a reduction in compressive strength from 1.9 to 1.5 GPa. Similarly, Fedulov et al (2015) reported a 16 % reduction in ultimate compression load for a fiber misalignment of 58 in carbon/epoxy composites, along with a linear reduction in failure initiation load due to misalignment. Furthermore, Vallons et al (2011) reported tensile property reductions for a biaxial non-crimp fabric composite at small off-axis angles.…”
Section: Adverse Effects Of Fiber Misalignment On Mechanical Propertiesmentioning
confidence: 85%
“…Depending on the manufacturing process, other types of defects can prove to be much more difficult to eliminate. LCM processes are associated with a number of specific manufacturing defects such as voids, dry spots, in-and out-of-plane fiber undulations, microcracks and part distortions (Fedulov et al, 2015;Hagstrand et al, 2005;Hamidi and Altan, 2017;Mukhopadhyay et al, 2015;Anders et al, 2016). As depicted in Fig.…”
Section: Defect Types In Lcmmentioning
confidence: 99%
See 3 more Smart Citations